Renewable Polymers from Passion Fruit Vegetable Oils Extracted by Different Methods - Carneiro, Victória R.A. [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael T.; Santos, Gabriel I. [UNESP]; Santos, Fernanda B. [UNESP]; Bannach, Gilbert [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
The vegetable oil extraction process can interfere with the characteristics of the final product, including color and unsaturated quantity. However, no study has analyzed this effect in vegetable oil-based polymeric materials. Therefore, this work evaluates two different extraction methods for passion fruit vegetable oil and their influence on polymeric materials, comparing the results with one polymer obtained by commercial vegetable oil. The polymers syntheses were performed in the absence of solvent nor catalyst and performed by conventional heating. Properties as iodine values and fatty acid profile did not vary significantly among the oils. However, color and thermal stability varied between the vegetable oils, especially due to the presence of small molecules that can be extracted during the Soxhlet process. As a result, the final polymers also presented different colors. For this type of polymerization, the extraction processes did not interfere significantly in thermal stability, glass transition, spectroscopic data nor morphological properties of final polymers.
Polímeros Renováveis obtidos a Partir de Óleos Vegetais de Maracujá Extraídos por Diferentes Métodos
Keywords: glycerol; Passion fruit vegetable; renewable polymers